2019
DOI: 10.1590/1677-5449.007318
|View full text |Cite
|
Sign up to set email alerts
|

Association between critical limb ischemia and arterial stiffness measured by brachial artery oscillometry

Abstract: Background Elevated arterial stiffness is associated with increased cardiovascular mortality. The relationship between arterial stiffness and critical limb ischemia (CLI) is not well established. Objectives The objective of this study is to analyze the relationship between arterial stiffness indices and the degree of limb ischemia measured by the ankle-brachial index (ABI). Methods A cross-sectional study comparing patients with CLI and controls. Arterial stiffness was measured using brachial artery oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
6
0
4
Order By: Relevance
“… 13 , 34 Moreover, elevated AS may be an indicator of high mortality in patients with PAD with claudication or severe ischemia. 35 On the contrary, a study in middle-aged Japanese men free of PAD reported that decreased AS is related to lower ABI. 19 This could be explained by the fact that AS (eg, baPWV) reflects the stiffening of central and peripheral muscular arteries, 36 which is closely correlated with but different from blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“… 13 , 34 Moreover, elevated AS may be an indicator of high mortality in patients with PAD with claudication or severe ischemia. 35 On the contrary, a study in middle-aged Japanese men free of PAD reported that decreased AS is related to lower ABI. 19 This could be explained by the fact that AS (eg, baPWV) reflects the stiffening of central and peripheral muscular arteries, 36 which is closely correlated with but different from blood pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown upregulation of HIF, VEGF, and VEGFR-2 in limb ischemia, especially in acute limb ischemia as opposed to chronic ( 102 , 103 ). Since limb ischemia is so similar to PAD, many of the mechanical changes present in PAD are also in ischemia, such as increased arterial stiffening and increased blood pressure ( 104 ). Studies have explored whether pro-angiogenic factors could promote vascularization in ischemic tissues, although so far these strategies have demonstrated mixed success, with single factors appearing to be less effective than combined treatments ( 93 , 105 , 106 ).…”
Section: Angiogenesismentioning
confidence: 99%
“…Increase of arterial stiffness is associated with higher risk for the development of arteriosclerosis and recognized as a prognostic marker beyond standard risk factors. Currently, arterial stiffness is able to be measured non-invasively and reproducibly [6–9] …”
Section: Introductionmentioning
confidence: 99%
“…Currently, arterial stiffness is able to be measured non-invasively and reproducibly. [6][7][8][9] To date, to evaluate vascular dysfunction, an early stage of arteriosclerosis, several devises have been developed. Pulse wave velocity (PWV) is widely used in clinical practice as a parameter for arterial stiffness.…”
Section: Introductionmentioning
confidence: 99%